Whatever Singularity, Negative Community, and Literature (Perhaps). Issue 1 (April 2016) - Tremblay, Thierry
Abstract : Evoking the eighteenth-century sources of the idea of 'negative community', this article refers to Georges Bataille's attempt to create a new community, or secret society: Acéphale . For his part, and writing after Maurice Blanchot's The Unavowable Community and Jean-Luc Nancy's The Inoperative Community, Giorgio Agamben articulates the idea of a 'coming community', which he calls the 'whatever singularity'. Doing so in the context of these influences, this article considers, particularly in its conclusion, the question of literature in the specific temporality brought by the potentiality of the negative.